Evaluation of ocular pulse amplitude and choroidal thickness in diabetic macular edema - Totan, Y; Akyüz, T K; Güler, E; Güragaç, F B (Eye (London), 2016)
Purpose The aim of this study is to evaluate the ocular pulse amplitude (OPA) and choroidal thickness (CT) measurements in patients with diabetic macular edema (DME) and healthy subjects. Methods A total of 34 patients (12 male and 22 female) who had type 2 diabetes mellitus with DME and 34 sex-matched healthy subjects (13 male and 21 female) were included in this prospective study. The intraocular pressure (IOP) and OPA were measured with Dynamic contour tonometer (Pascal DCT, Switzerland). The subfoveal CT was measured using the Cirrus HD-OCT (Carl Zeiss Meditec). The CT at 1500 μ m and 3000 μ m nasal and temporal to the central fovea was also measured. Results The mean IOP values were 18.4±3.5 and 17.1±2.1 mm Hg in DME patients and healthy controls, respectively ( P = 0.091). The mean OPA values in patients with DME (2.58±0.96) and controls (3.52±1.03) were statistically different ( P <0.001). The mean subfoveal CT value was 273.5±30.2 μ m in the eyes with DME and 321.4±36.5 μ m in the control group ( P < 0.001). In both groups, linear regression analysis showed no significant association between OPA and CT measurements. The IOP showed a significantly positive correlation with OPA in both DME ( P =0.002, r =0.526) and controls ( P =0.004, r =0.483). Conclusions The current study suggests that both pulsatile choroidal blood flow and CT are decreased in patients with DME.